Effect of Unstable Mix under Severe Traffic Loading on Performance of Asphalt Pavements in Tropical Climate - Rodgers B. Mugume (Advances in Civil Engineering)
This paper is aimed at assessing the in-service performance of asphalt pavements in tropical climate under severe conditions. The main defect observed on the asphalt pavement was rutting of the asphaltic surfacing, with top-down cracking being experienced on a few sections and not widespread but rather intermittent. Field and laboratory investigations were conducted as well as a review of design and construction records. The defects observed were confined to the wearing course layer of the surfacing with the other underlying layers performing well. Rutting was a result of heavily loaded trucks that moved at very slow speeds due to steep gradients, hence resulting in severely loaded sections. High temperatures due to the warm tropical environment exacerbated the situation and caused the asphalt to flow, hence resulting in rutting and deformation. Also, low air voids in the asphalt mix which were below the recommended design air voids specification aggravated the situation as well as the air voids after refusal density compaction being below the specified critical minimum of 3% after secondary compaction. Top-down cracking was due to binder age hardening and embrittlement resulting from overheating of bitumen during the construction process coupled with heavy truck axles and high tyre pressures. Defects observed, therefore, resulted from an unstable asphalt mix that was not suitable for severe loading conditions; hence, the asphalt concrete laid was out of specification. The Modified Marshall Mix Design method should be used for severe sites where slow speed or heavier traffic is expected.